The impact of environmental and dietary exposure on gestational diabetes mellitus: a comprehensive review emphasizing the role of oxidative stress - Sun, Congcong; Shen, Jiaying; Fang, Rujing; Huang, Huiya; Lai, Yanan; Hu, Yanjun; Zheng, Jianqiong (Frontiers in Endocrinology, 2025)
Gestational diabetes mellitus (GDM) is a common pregnancy complication closely associated with maternal oxidative and antioxidant imbalance, known as oxidative stress. Environmental and dietary exposure plays an important role in inducing oxidative stress during pregnancy. This review aims to provide an in-depth analysis of the role of oxidative stress induced by environmental and dietary exposure in GDM while incorporating current research frontiers. Environmental pollution, smoking, excessive nutrition, and unhealthy eating habits such as a high-fat diet and vitamin deficiency, may contribute to the generation and accumulation of reactive oxygen species (ROS), leading to oxidative stress. Within the pathway of oxidative stress in GDM, the production and clearance mechanisms of ROS play a pivotal role. Relevant studies have demonstrated that ROS production is closely linked to insulin resistance, adipose tissue accumulation, inflammation, and other pathological processes. Antioxidant substances like vitamins C and E or glutathione can mitigate oxidative stress damage on pregnant women and fetuses by scavenging ROS. Currently, there remain several cutting-edge issues regarding the involvement of the oxidative stress pathway in GDM pathogenesis as well as its relationship with environmental and dietary factors, for instance: how to reduce maternal oxidative stress levels through dietary adjustments or lifestyle modifications; how antioxidant substances can be utilized for intervention treatment; and accurate assessment methods for maternal oxidative stress status along with its association with GDM risk. In conclusion, environmental and dietary factors exert significant influence on GDM pathogenesis while highlighting increasing attention toward understanding the role played by the oxidative stress pathway within this context. In-depth research endeavors within this field are anticipated to offer novel insights into prevention strategies as well as therapeutic approaches for GDM.